Pengaruh Brand Ambassador, Citra Merk dan Kualitas Produk terhadap Keputusan Pembelian Produk Kecantikan Ms Glow - Purnomo, Nanto; Rasyidah, Fadilatur (BUDGETING : Journal of Business, Management and Accounting, 2024)
ABSTRACT This study aims to investigate the influence of brand ambassadors, brand image, and product quality on the purchasing decision of MS Glow beauty products. The data analysis method used descriptive statistical analysis and multiple linear regression analysis. The results show that there is a significant and positive influence of brand ambassadors, brand image, and product quality on the purchasing decision of MS Glow beauty products. Brand ambassadors, brand image, and product quality together contribute to increasing the number of purchasing decisions by consumers. The implications of this study emphasize the importance for companies to pay attention to marketing strategies through brand ambassadors, building a positive brand image, and maintaining product quality to enhance the attractiveness and trust of consumers in MS Glow beauty products. Keywords: Brand Ambassador, Brand Image, MS Glow, Product Quality, Purchasing Decisions.